Penentuan Kadar Tanin Pada Daun Cempedak (Artocarpus Champeden L.) Secara Permanganometri - Rendra Okta Yulfa (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2023)
Tannins are active compounds of secondary metabolites which are known to have several properties, namely as an astringent, anti-diarrheal, and antibacterial. Tannin compounds can be found in cempedak leaves (Artocarpus champeden L). In this study, the determination of tannin content in cempedak leaves (Artocarpus champeden L) was carried out. Determination of tannin content in cempedak leaves was carried out using the permanganometric method. From the results of the determination of the content, it showed that the tannin content in the decoction of cempedak leaves was 5.0203% w/w permanganometrically